Genetic characterization of mung bean (Vigna radiata) genotypes based on morphological traits and SSR markers - Samyuktha, S M; Karthikeyan, A; Dhasarathan, M; Senthil, N; Juliet Hepziba, S; Malarvizhi, D (Plant Science Today, 2025)
The genetic diversity among 117 mung bean (Vigna radiata) accessions was assessed using eight morphological traits and 70 Simple Short Repeat (SSR) markers. These accessions were grown in an augmented design during the Summer and Kharif seasons of 2017. The mean data from the two seasons were subjected to correlation, principal component and cluster analyses. Plant height (r = 0.527), the number of pods in a plant (r = 0.717) and the number of seeds in a pod (r = 0.241) showed a highly significant positive relationship with individual plant yield. Principal Component Analysis (PCA) revealed that the first three components explained 74.32 % of the total variation, with eigenvalues greater than one. Principal Component 1 (PC1) accounted for the maximum variation in traits, including days to first flowering (loading = 0.773), days to 50 % flowering (0.740), number of pods in a plant (0.708) and plant height (0.653). Morphological trait-based clustering grouped the genotypes into two major clusters. Further, the 117 mung bean accessions were analyzed using 70 SSR markers. Of the 70 SSRs, thirteen were polymorphic and generated 55 alleles, averaging 4.23 alleles per locus. The polymorphic information content (PIC) values ranged between 0.52 and 0.79, averaging 0.71. Analysis of genotypic data led to the classification of the accessions into three clearly defined clusters. The findings of the present study were expected to contribute to future mung bean breeding programs aimed at developing trait-specific genotypes.